1954
DOI: 10.1002/jctb.5010041004
|View full text |Cite
|
Sign up to set email alerts
|

Distribution experiments and liquid‐liquid equilibrium in systems containing nicotine

Abstract: Distribution coefficients at 25° for nicotine between water and three organic solvents for low nicotine concentrations have been determined. The liquid‐liquid equilibrium at 25° for the system nicotine‐water‐carbon tetrachloride has been investigated, and it is shown that the system is solutropic, with a horizontal tie‐line at 38 wt.‐% of nicotine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1957
1957
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Some authors have already reported LLE data for the systems consisting of chloroform and carbon tetrachloride. 35−48 Acetone, 35 nicotine 36 acetic acid, 38,46 and tetrahydrofuran 39 were purified using carbon tetrachloride and acetic acid, 37,42,43 while tetrahydrofuran, 39 valeric acid, pyruvic acid, propionic acid, 43 acetyl acetone, 44 and 2-methylaziridine 47 were separated using chloroform. Mixtures of chloroform with other solvents (toluene or diethyl ether) were also used to separate ethanol from water.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors have already reported LLE data for the systems consisting of chloroform and carbon tetrachloride. 35−48 Acetone, 35 nicotine 36 acetic acid, 38,46 and tetrahydrofuran 39 were purified using carbon tetrachloride and acetic acid, 37,42,43 while tetrahydrofuran, 39 valeric acid, pyruvic acid, propionic acid, 43 acetyl acetone, 44 and 2-methylaziridine 47 were separated using chloroform. Mixtures of chloroform with other solvents (toluene or diethyl ether) were also used to separate ethanol from water.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, two chlorinated methanes (tri and tetra chloromethane) were chosen as solvents to investigate the liquid–liquid equilibria of ternary systems (water + OPA + chloroform) and (water + OPA + carbon tetrachloride). Some authors have already reported LLE data for the systems consisting of chloroform and carbon tetrachloride. Acetone, nicotine acetic acid, , and tetrahydrofuran were purified using carbon tetrachloride and acetic acid, ,, while tetrahydrofuran, valeric acid, pyruvic acid, propionic acid, acetyl acetone, and 2-methylaziridine were separated using chloroform. Mixtures of chloroform with other solvents (toluene or diethyl ether) were also used to separate ethanol from water. , …”
Section: Introductionmentioning
confidence: 99%